Evaluation of cardiovascular risk in climacteric women: A cross-sectional study - Martha Pantel dos Santos Mota; Isabel Cristina Gomes Moura; Ricardo Mello Marinho; Eduardo Back Sternick; Alessandra Maciel Almeida (Wolters Kluwer Medknow Publications, 2018)
Purpose: To identify cardiovascular risk factors in women between 40 and 65 years old in two private clinic of gynecology in Minas Gerais. Methods: Cross-sectional study from January/2016 to January/2017 in 137 climacteric women. A standardized questionnaire was used to evaluate socio-demographic characteristics, climacteric phases, cardiovascular risk factors, menopause (age, time and type), number of pregnancies, normal births, abortions, partners and hormonal therapy. The evaluation model was used according to the Framingham risk score. Results: The median age was 47 years, and 35% were postmenopausal. The majority were married and 42.3% caucasian. Abdominal circumference greater than 80 cm was observed in 87.6%, and greater than 88 cm in 67.2%. High total cholesterol (TC) was observed in 48.2%. Low levels of high-density lipoprotein (HDL-c) were observed in 42.3%. Elevated levels were observed for low density lipoprotein (LDL-c) in 39.4%, triglycerides in 29.9%, and fasting glucose in 8.8%. Also, systolic and diastolic blood pressure were considered high in 25.5% cases. Postmenopausal women presented higher values of TC and HDL-c. Analysis of the Framingham risk score revealed a higher cardiovascular risk for postmenopausal women. Higher values of waist circumference, glycemia and triglycerides were observed for women with higher cardiovascular risk. Conclusions: Postmenopausal women had a higher risk of cardiovascular events when compared to premenopausal ones.